Headmaster controlling di sekolah menengah kejuruan Payakumbuh - Resmanti, Pepi; Giatman, Muhammad; Ernawati, Ernawati (JRTI (Jurnal Riset Tindakan Indonesia), 2022)
The background of this research was writer observation at SMK Negeri 3 Payakumbuh. The result of observation  showed that: still low headmaster controlling at there.The aim of this research was get information about the controlling headmaster at SMK Negeri 3 Payakumbuh.The populations of this research were civil servant teachers at SMK Negeri 3 Payakumbuh as many as 48 peoples and the sample were 38 peoples servants that taken by Stratified Proportional Random Sampling with Cochran’s formula. The instrument of this research was questionares with Likert scale model which has proven it validity and reliability. The results of this research showed that: leader controlling was in good categories (85%). It can be concluded that there were headmaster controlling to servants performance at SMK Negeri 3 Payakumbuh was in good categories (85%).